KEMAMPUAN TEKNIK PERSONAL SISTEM INFORMASI, UKURAN ORGANISASI, KETERLIBATAN PEMAKAI DALAM SISTEM TERHADAP KINERJA SISTEM INFORMASI AKUNTANSI - Prapti Ningsih; Danang Mintoyuwono; Wianda Bias Intan Sepvie (JIAFE (Jurnal Ilmiah Akuntansi Fakultas Ekonomi), 2019)
This research was conducted to examine the effect of the technical ability of personal information systems, organizational size, user involvement in the system on the performance of accounting information systems. The population in this study includes all employees who use accounting information systems, namely tellers and back offices in conventional banks in the South Jakarta area. The sampling method used in this study is Simple Random Sampling. The final data generated are 48 samples that are ready to be analyzed and tested. The analysis technique used is multiple linear regression and uses the name of the SPPS statistical application with a significance level of 5%. The results of this study indicate that (1) the technical ability of personal information systems has a significant influence on the performance of accounting information systems, (2) the size of the organization has no significant effect on the performance of accounting information systems, (3) user involvement in the system has a significant influence on accounting performance information Systems.